2021
DOI: 10.1371/journal.pone.0261720
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled ciprofloxacin-loaded poly(2-ethyl-2-oxazoline) nanoparticles from dry powder inhaler formulation for the potential treatment of lower respiratory tract infections

Abstract: Lower respiratory tract infections (LRTIs) are one of the fatal diseases of the lungs that have severe impacts on public health and the global economy. The currently available antibiotics administered orally for the treatment of LRTIs need high doses with frequent administration and cause dose-related adverse effects. To overcome this problem, we investigated the development of ciprofloxacin (CIP) loaded poly(2-ethyl-2-oxazoline) (PEtOx) nanoparticles (NPs) for potential pulmonary delivery from dry powder inha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 53 publications
7
28
0
Order By: Relevance
“…The average particle size of the original blank PEtOx NPs is about 196.7 ± 24.0 nm and 5 mg and 25 mg CIP-loaded PEtOx NPs are 299.7 ± 18.2 nm and 200.0 ± 22.0 nm, respectively, as reported previously [ 17 ]. Stored blank and CIP-loaded PEtOx NPs’ average particle size and size distribution are presented in Figure 1 and Figure 2 , respectively, compared with freshly prepared samples.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The average particle size of the original blank PEtOx NPs is about 196.7 ± 24.0 nm and 5 mg and 25 mg CIP-loaded PEtOx NPs are 299.7 ± 18.2 nm and 200.0 ± 22.0 nm, respectively, as reported previously [ 17 ]. Stored blank and CIP-loaded PEtOx NPs’ average particle size and size distribution are presented in Figure 1 and Figure 2 , respectively, compared with freshly prepared samples.…”
Section: Resultssupporting
confidence: 83%
“…In both studies, the stored formulations demonstrated comparably stable states at low temperatures and RH. Thus, particle-engineered techniques have been applied to develop more stable formulations in adverse conditions including spray-dried particles, drug-polymer conjugates and drug-loaded polymeric NPs [ 15 , 16 , 17 ]. However, it is still very important to determine the optimized conditions to store the DPI formulations to retain their aerosolization properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the poorly water-soluble fenofibrate showed faster dissolution from the PEtOx matrix compared to the pure API. After this first report on using PAOx as excipient for drug formulation, various PAOx grades have been demonstrated for the efficient preparation of solid dosage forms [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. However, to the best of our knowledge, PAOx have not been reported as excipient for sustained release formulations despite that they appear to be ideally suited for this purpose based on the tunability of their physical properties in combination with a good processability.…”
Section: Introductionmentioning
confidence: 99%